A Blood Test for MethylatedBCAT1andIKZF1vs. a Fecal Immunochemical Test for Detection of Colorectal Neoplasia. Issue 1 (January 2016) - Symonds, Erin L; Pedersen, Susanne K; Baker, Rohan T; Murray, David H; Gaur, Snigdha; Cole, Stephen R; Gopalsamy, Geetha; Mangira, Dileep; LaPointe, Lawrence C; Young, Graeme P
Abstract : OBJECTIVES: : To compare the performance of a new blood test for colorectal cancer (CRC) to an established fecal immunochemical test (FIT) in a study population with the full range of neoplastic and non‐neoplastic pathologies encountered in the colon and rectum. METHODS: : Volunteers were asked to complete a FIT prior to colonoscopy. Blood was collected after bowel preparation but prior to colonoscopy, and plasma was assayed for the presence of methylated BCAT1 and IKZF1 DNA using a multiplex real‐time PCR assay. Sensitivity and specificity estimates for the blood test were calculated from true‐ and false‐positive rates for neoplasia and compared with FIT at a range of fecal hemoglobin (Hb) concentration positivity thresholds. RESULTS: : In total, 1, 381 volunteers (median age 64 years; 49% male) completed both tests prior to colonoscopy. Estimated sensitivity of the BCAT1/IKZF1 blood test for CRC was 62% (41/66; 95% confidence interval 49–74%) with a specificity of 92% (1207/1315; 90–93%). FIT returned the same specificity at a cutoff of 60 μg Hb/g, at which its corresponding sensitivity for cancer was 64% (42/66; 51–75%). In the range of commonly used FIT cutoffs, respective cancer sensitivity and specificity estimates with FIT were: 59% (46–71%) and 93% (92–95%) at 80 μg Hb/g, and 79% (67–88%) and 81% (78–83%) at 10 μg Hb/g. Although estimated sensitivities were not significantly different between the two tests for any stage of cancer, FIT showed a significantly higher sensitivity for advanced adenoma at the lower cutoffs. Specificity of FIT, but not of the BCAT1/IKZF1 blood test, deteriorated substantially in people with overt blood in the feces. When combining FIT (cutoff 10 μg Hb/g) with the BCAT1/IKZF1 blood test, sensitivity for cancer was 89% (79–96%) at 74% (72–77%) specificity. CONCLUSIONS: : A test based on detection of methylated BCAT1 / IKZF1 DNA in blood has comparable sensitivity but better specificity for CRC than FIT at the commonly used positivity threshold of 10 μg Hb/g. Further evaluation of the new test relative to FIT in the population screening context is now required to fully understand the potential advantages and disadvantages of these biomarkers in screening.